Targeting the Hexosamine Biosynthetic Pathway Prevents Plasmodium Developmental Cycle and Disease Pathology in Vertebrate Host - Gomes, Pollyanna Stephanie; Tanghe, Scott; Gallego-Delgado, Julio; Conde, Luciana; Freire-de-Lima, Leonardo; Lima, Ana Carolina; Freire-de-Lima, Célio Geraldo; Lima Junior, Josué da Costa; Moreira, Otacílio; Totino, Paulo; Rodriguez, Ana; Todeschini, Adriane Regina; et al. (Frontiers in Microbiology, 2019)
Cerebral malaria (CM) is a clinical syndrome involving irreversible and lethal signs of brain injury associated to infection by parasites of the genus Plasmodium. The pathogenesis of CM derives from infection-induced proinflammatory cytokines associated with cytoadherence of parasitized red blood cells to brain microvasculature. Glycoconjugates are very abundant in the surface of Plasmodium spp and are critical mediators of parasite virulence in host-pathogen interactions. Herein, we show that 6-Diazo-5-oxo-L-norleucine (DON) therapeutically used for blocking hexosamine biosynthetic pathway leads to recovery in experimental murine cerebral malaria. DON-induced protection was associated with decreased parasitism, which severely reduced Plasmodium transmission to mosquitoes. These findings point to a potential use of DON in combination therapies against malaria.